ORAL HEALTH-RELATED QUALITY OF LIFE AND CARIES EXPERIENCE AMONG YOUNG ADULTS - Ștefana Maria Cozma; Livia Bobu; Elena-Raluca Baciu; Gabriela Luminița Gelețu; Roxana-Ionela Vasluianu; Simona Stoleriu; Alice Murariu (Romanian Dental Association for Education, 2023)
Young adults represent the age group with the highest ability to understand the need of maintaining good oral health and the highest chance to adopt correct oral hygiene behaviors. Great attention should also be paid to risk factors for oral conditions, especially sugary aliments intake, which creates a suitable environment for developing dental caries. Young adults should be aware about the importance of reducing the frequency of consumption of these aliments. Smoking has negative effects on both general and oral health. It creates and maintains conditions favorable for developing oral diseases. Quitting smoking should be seen as an important recommendation, to ensure good oral health and quality of life. The impairment of oral health is strongly connected with quality of life. To quantify the impact of oral health on quality of life, the OHIP-14 questionnaire is widely used. Regarding the severity of the impact oral conditions have on quality of life, the most accused domains by subjects are physical pain, psychological discomfort and psychological disability. Oral health is directly influenced by caries experience, OHRQoL being lower as the caries prevalence is higher. To quantify the prevalence of dental caries, the DMFT index is one of the most used indicators. It evaluates, on one hand, the caries experience, and on the other hand, the exact number of decayed, missing and filled teeth. OHRQoL is a mandatory toll that helps understand the impact of oral conditions on general health. Both the OHIP-14 questionnaire and the DMFT index, are a real help to quantify the connection between oral conditions, most common of them being dental caries, and their negative effects on general health and on quality of life.